ISSUE REGARDING THE EMPLOYMENT OF DISABLED PEOPLE ON THE WAY TO EUROPEAN INTEGRATION - Vorozhbiian, М.; Ivashchenko, М.; Skrypnyk, О.; Rogozin, А. (Municipal economy of cities (Technical science), 2023)
The article examines problems that, in connection with the increase in the number of disabled people as a result of the war in Ukraine, are becoming even more urgent and indicate the need for a comprehensive approach to their solution, taking into account European experience and European Union standards. The right to work of persons with disabilities is guaranteed, first of all, by the Constitution. In addition, today laws are in force in Ukraine and a number of international acts have been ratified, which should prevent discrimination of persons with disabilities in the field of employment. As of September 1, 2017, the Association Agreement between Ukraine and the European Union entered into force, namely: in accordance with Annex XL of the Agreement, Ukraine undertakes to gradually bring its legislation closer to the legislation within the established deadlines. Of the total number of persons with disabilities, almost half are of working age and need rehabilitation and further employment. Therefore, the nature of the workplace, the method of adapting it to the needs of a person with a disability comes to the fore. One of the main obstacles in a full-fledged social life and, in particular, in the employment of disabled people, is the lack of accessibility. Social accessibility involves ensuring decent conditions for the participation of individuals and social groups in the life of communities. Access to education is one of the main barriers to access to employment. Special attention should be paid to the organization of workplaces for the disabled by the state, which organizes professional and labor rehabilitation taking into account the experience of European countries. Now, in the period of digitalization, there are unique opportunities for training the disabled, in particular remotely, and obtaining new professions, including in the field of IT technologies. The transition of a number of businesses to remote work opens up new opportunities for organizing workplaces for people with disabilities at home for remote work, while taking into account all the recommendations of the Medical and Social Expert Commission. Given the status of a candidate for the European Union, Ukraine faces the task of accelerating the adaptation of the legislative framework to European standards. It is necessary to strengthen cooperation in solving the issues of professional rehabilitation of disabled people and their employment between medical experts, labor and social protection bodies, employers, with the aim of coordinating and consolidating joint efforts to solve the tasks of creating an effective system of promoting the employment of disabled people.